The Relationship Between Objective Family Burden And Family Ability To Care For Schizophrenia - Suharsono; Irmawati, Nurisda Eva; Aprilianisari, Erita (Journal of Applied Nursing and Health, 2024)
Background: Schizophrenia is one mental illness type. Family interactions are impacted by this disease because it leads individuals to behave erratically. Family caregivers will be less able to care for patients because of the strain this condition puts on them. The researchers at Dr. Amino Gondohutomo Hospital in Central Java Province set out to find out how family caregivers' capacity to care for their loved ones with schizophrenia correlated with their own subjective burdens. Methods: Using a cross-sectional method and a purposive sample technique, this study utilized a quantitative correlational type with a maximum of 38 respondents. A family burden questionnaire and the ability to care for one's family using the Spearman Rank test were the research instruments used. Results: The Spearman Rank test results reveal a significant value of 0.008 <0.05 between the objective load of the family and the ability to care for the family, and a unidirectional correlation coefficient value of -0.427 between the two variables. Conclusion: The conclusion of this study is that there is a significant relationship, and the higher the perceived burden, the worse the family's ability to care. It is recommended to provide support and resources to families to alleviate their perceived burden, thereby enhancing their ability to provide effective care